The Role of Musyrif Leadership in Improving the Quality of Students’ Learning at Ibnu Abbas Tahfizhul Qur’an Islamic Boarding School, Klaten - Ariyanto; Sukari (At Turots: Jurnal Pendidikan Islam, 2026)
This study examines the role of musyrif leadership in improving the quality of students’ learning at Pondok Pesantren Tahfizhul Qur’an Ibnu Abbas Klaten. The research employed a quantitative descriptive approach to analyze the contribution of musyrif leadership in fostering effective learning processes among santri. The primary objective of this study was to identify the extent to which musyrif leadership influences learning quality, including discipline, motivation, and academic achievement of santri. The research methodology involved a survey method using structured questionnaires distributed to 30 santri as the research sample. Data were analyzed using descriptive statistical techniques to obtain percentage-based interpretations. The findings indicate that 83.3% of respondents perceived musyrif leadership as highly effective in improving learning quality, 10.0% rated it as moderately effective, while 6.7% considered it less effective. Furthermore, the results reveal that musyrif leadership significantly contributes to enhancing learning discipline (86.7%), increasing learning motivation (80.0%), improving understanding of religious materials (76.7%), and strengthening students’ moral and character development (90.0%). In conclusion, musyrif leadership plays a crucial role in improving the quality of learning at Islamic boarding schools, particularly in tahfizh-based institutions. This study recommends strengthening leadership training programs for musyrif to ensure sustainable improvement in educational quality.